Cervical Spine Deformity—Part 2: Management Algorithm and Anterior Techniques - Tan, Lee A.; Riew, K. Daniel; Traynelis, Vincent C. (Neurosurgery, 2017)
Abstract A sound operative plan based on solid understanding of the pathology and biomechanics is the most important part of cervical deformity correction. Many different surgical options exist for operative management of cervical spine deformities. However, selecting the correct approach that ensures the optimal clinical outcome can be challenging and often controversial. In Part 2 of this three-part review series, we discuss the pre-operative planning, management algorithm, and anterior surgical techniques for cervical deformity correction.